The Correlation of Interest in Becoming a Teacher with Learning Outcomes in the Educational Field of Automotive Engineering Education Students - Ahmad Arif; Nizwardi Jalinus; Refdinal Refdinal; Hasan Maksum; Martias Martias; Toto Sugiarto; M. Yasep Setiawan; Yuke Permata Lisna (AEEJ : Journal of Automotive Engineering and Vocational Education, 2022)
The student's desire to become a teacher is a factor that influences attitudes and motivation to attend lectures. High levels of interest in becoming a teacher will speed up the lecture process and influence student learning outcomes. The purpose of this correlational study is to determine the relationship between student learning outcomes in education courses and interest in becoming a teacher. The study was conducted on students from the FT UNP Automotive Engineering Education study program's 2018 class. The study was conducted on students from the FT UNP Automotive Engineering Education study program's 2018 class. The Pearson product moment correlation formula was used to analyze the data, and the t test was used to determine the significance of the correlation coefficient r. Based on the analysis of the research data, it was determined that there is a positive and significant relationship between desire to become a teacher and learning outcomes in student education courses.